Hubungan Kemampuan Literasi Awal Anak Usia 5–6 Tahun Berdasarkan Durasi Penggunaan Gawai di Rumah - Zahra Aulia Hidayati; Sinta Auliya; Gina Zahra Febriyanti; Budi Iskandar (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
The rapid development of digital tecnology has increased gadget use among early childhood children. In everyday life, gadgets are not only used as entertainment media, but also as learnig tools that may influence children’s early literacy development. This study aimed to determine the relationship between the duration of gadget use at home and the early literacy skills of children aged 5-6 years. The study employed a quantitative approach with a correlational ex-post facto design. The particopants consisted of 17 children enrolled at TK Ihya As-Sunnah Tasikmalaya, selected using saturated sampling techniques. Data on gadget usage duration were collected through questionnaires completed by parents, while children’s early literacy abilities were measured using obsevation sheets. Data analysis was carried out using descriptive statistics and the Spearman Rank correlation test. The findings showed that the average duration of gadget use among children was 1.755 hours per day, while the average early literacy score reached 24.24. the correlation analysis indicated a negative but weakand statistically insignificant relationship between gadget use duration and early literacy ability (r = -0.335; p > 0.05). these results suggest that gadget use duration alone does not directly determine children’s literacy deveplopment. Other factors, such as parental assistance, quality og digital content, ank stimulation from the surrounding environment, also play important roles in supporting early literacy skills in children